Investigation Into Some Physiological Parameters Of Cotton Under Water Stress - Kumar, V; Mehta, N P; Gohil, M D (Annals of Arid Zone, 2016)
Two cotton varieties, G. Cot. 10 (G. hirsutum L.) and G. Cot. 11 (G. herbaceum L/) were subjected to water stress during 75-130 days after emergence. Total leaf area and dry weight of shoot reduced drastically, more in G. Cot 10 than in G. Cot. 11. The per cent decrease in root weight was more prononuced in G. Cot. 11. The specific leaf weight, however, increased, more in G, Cot. 11 than in G. Cot. 10, Higher amounts of free proline, free amino acids. chlorophyll and K accumulated under stress in the leaves of G. Cot. 11 imparted it greater degree af stress tolerance through high osmoticum, The values of nitrate reductase and relative water content, despite more in vivo decline in G. Cot. 11 remained higher than those in G. Cot 10.